Skrining dan Edukasi Penyakit Metabolik Melalui Pemeriksaan Glukosa Darah, Asam Urat, dan Kolesterol di Desa Mayangan Jombang - Evi Puspita Sari; Anthofani Farhan; Muhammad Badrut Tamam (Yayasan Daarul Huda Kruengmane, 2026)
Metabolic diseases such as diabetes mellitus, hyperuricemia, and hypercholesterolemia have become a significant global health burden, particularly among adults. Low awareness in rural communities regarding routine health check-ups remains a major obstacle to controlling non-communicable diseases. This community service activity aimed to map the health risk profile of residents of Mayangan Village through screening of blood glucose, uric acid, and cholesterol levels. The method used was a descriptive observational approach with direct examinations employing Point of Care Testing (POCT) devices. The results showed variations in metabolic conditions among 25 respondents, with several cases presenting values above reference levels that required further medical follow-up. This screening proved effective as an early educational instrument to encourage healthier lifestyle changes within the community.